Time of Day-Dependent Alterations in Hippocampal Kynurenic Acid, Glutamate, and GABA in Adult Rats Exposed to Elevated Kynurenic Acid During Neurodevelopment - Wright, Courtney J.; Rentschler, Katherine M.; Wagner, Nathan T. J.; Lewis, Ashley M.; Beggiato, Sarah; Pocivavsek, Ana (Frontiers in Psychiatry, 2021)
Hypofunction of glutamatergic signaling is causally linked to neurodevelopmental disorders, including psychotic disorders like schizophrenia and bipolar disorder. Kynurenic acid (KYNA) has been found to be elevated in postmortem brain tissue and cerebrospinal fluid of patients with psychotic illnesses and may be involved in the hypoglutamatergia and cognitive dysfunction experienced by these patients. As insults during the prenatal period are hypothesized to be linked to the pathophysiology of psychotic disorders, we presently utilized the embryonic kynurenine (EKyn) paradigm to induce a prenatal hit. Pregnant Wistar dams were fed chow laced with kynurenine to stimulate fetal brain KYNA elevation from embryonic day 15 to embryonic day 22. Control dams (ECon) were fed unlaced chow. Plasma and hippocampal tissue from young adult (postnatal day 56) ECon and EKyn male and female offspring were collected at the beginning of the light (Zeitgeber time, ZT 0) and dark (ZT 12) phases to assess kynurenine pathway metabolites. Hippocampal tissue was also collected at ZT 6 and ZT 18. In separate animals, in vivo microdialysis was conducted in the dorsal hippocampus to assess extracellular KYNA, glutamate, and γ-aminobutyric acid (GABA). Biochemical analysis revealed no changes in peripheral metabolites, yet hippocampal tissue KYNA levels were significantly impacted by EKyn treatment, and increased in male EKyn offspring at ZT 6. Interestingly, extracellular hippocampal KYNA levels were only elevated in male EKyn offspring during the light phase. Decreases in extracellular glutamate levels were found in the dorsal hippocampus of EKyn male and female offspring, while decreased GABA levels were present only in males during the dark phase. The current findings suggest that the EKyn paradigm may be a useful tool for investigation sex and time-dependent changes in hippocampal neuromodulation elicited by prenatal KYNA elevation, which may influence behavioral phenotypes and have translational relevance to psychotic disorders.